The protection of children victims of electronic harassment in criminal law: Controversial issues and possible de lege ferenda amendments - Paunović Nikola (Temida, 2020)
In the information society, everyday use of information and communication technology by children occupies a significant place in their lives. Technology has enabled children’s access to cyberspace where they can perform their daily school and leisure activities. However, children’s access to information technology has also created new opportunities for the emergence of different forms of electronic harassment. The subject of this paper includes the analysis of the following electronic forms of harassment of children: 1) grooming, 2) cyberstalking, 3) cyberbullying and 4) trolling. The main goal of the paper is to discuss the controversial issues in conceptualisation of the analyzed electronic forms of harassment of children. In addition, the subject of this paper includes the overview of the relevant legal framework regarding electronic forms of harassment of children at international, European and national level to determine whether these forms of harassment are recognized as criminal offences and to identify legal gaps in observed criminal law frameworks. In the concluding remarks, it is pointed out that incidents of electronic harassment of children are increasing, creating a necessity for new policies and laws to ensure better protection of children in cyberspace.